Analysis of the factors that determine cinema attendance. (3rd August 2022) - Batlle-Beltrán, Marta; Mateo, Manuel
New forms of consumption, including online streaming, have interfered with film exhibition, promoting important changes. These services need to generate significant traffic and a look for a wide range of home subscribers to provide them with an extensive catalogue of movies. The domestic confinement in almost all countries caused by COVID-19 has led the internet to break historical traffic records. Cinemas are no longer the only place where a film can be shown. The novelty of films is the main factor that convinces viewers to pay for a cinema ticket. The exhibitor must pursue excellence and offer a truly superior experience at a reasonable price, because of the limited budget for leisure activities. This research uses structural equation modelling (SEM) to carry out an empirical analysis on the results of a questionnaire with a focus on the factors influencing the preference for watching films at a cinema.